Thermodynamic investigation of nanoplastic aggregation in aquatic environments - Kim, Min Ji; Herchenova, Yuliia; Chung, Jae shik; NA, SANG HEON; Kim, Eun Ju (Elsevier BV, 2022)
In this study, the aggregation behavior of polystyrene nanoplastics (PS NPs) in the absence or presence of oppositely charged particulate matters is systematically investigated for a wide range of electrolyte conditions. Herein, we used isothermal titration calorimetry combined with time-resolved dynamic light scattering to provide kinetic and thermodynamic insights into the NP aggregation. The thermodynamic profiles of homoaggregation and heteroaggregation were fit using an independent site and two independent sites models, respectively, demonstrating different interaction modes of both aggregation processes. We found that the contribution of solvation entropy was significant and variable in most cases, and this thermodynamic parameter was a large determinant of the thermodynamics of NP aggregation. Furthermore, the stability of PS NPs in natural water matrices was found to be correlated with ionic strength and the content of natural colloids (e.g., metal oxides and clay particles). These results point to the importance of considering the role of thermodynamic variables when studying the fate of NPs within various environmental conditions.